2016
DOI: 10.1016/j.biomaterials.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Human astrocytic grid networks patterned in parylene-C inlayed SiO2 trenches

Abstract: Recent literature suggests that glia, and in particular astrocytes, should be studied as organised networks which communicate through gap junctions. Astrocytes, however, adhere to most surfaces and are highly mobile cells. In order to study, such organised networks effectively in vitro it is necessary to influence them to pattern to certain substrates whilst being repelled from others and to immobilise the astrocytes sufficiently such that they do not continue to migrate further whilst under study. In this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…The parylene-C patterning technique was also applied to other cell types, such as the human teratocarcinoma cell line [20], achieving pattern fidelity with single-cell resolution [21]. Recent studies even demonstrated Ca 2+ transients in astrocytic networks patterned in parylene-C trenches [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The parylene-C patterning technique was also applied to other cell types, such as the human teratocarcinoma cell line [20], achieving pattern fidelity with single-cell resolution [21]. Recent studies even demonstrated Ca 2+ transients in astrocytic networks patterned in parylene-C trenches [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The parylene-C/SiO 2 platform has found utility in patterning neurons and glia, motivated by the need to precisely control the location of neuronal cell bodies at the interface of multi-electrode arrays and to control the connectivity within networks of neurons and astrocytes [612]. Delivopoulos et al and Unsworth et al generated patterned co-cultures of murine neurons and glia [6, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hughes et al demonstrated patterning of LUHMES neuronal networks by first patterning a template of glial-like stem cells on parylene-C/SiO 2 substrates [10]. More recently, human neurons and astrocytes, which were derived from the NTera2.D1 (hNT/NT2) cell line, have been patterned by Unsworth et al, Jordan et al, and Raos et al [7, 9, 11, 12]. The NT2 (hNT) cell line provides a readily available source of neurons and astrocytes that are more applicable to human physiology than primary cells of non-human origin [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, astrocytes cultured on the tall pillars were less migratory and proliferative on these pillars, suggesting that surface patterning can be used to alter astrocyte behavior. Grid networks composed of SiO 2 grids inlaid with biocompatible parylene-C have also been developed to study astrocyte interactions from single cell to the network level [Jordan et al, 2016]. While more work needs to be done in this field, the study showed the feasibility of this approach to pattern astrocytes in a grid network.…”
Section: Introductionmentioning
confidence: 99%